Self-regulation as a context of critical thinking in cyberpolice officers (Law and Safety, 2021)
The results of a study of self-regulation in the context of critical thinking in cyberpolice are presented. It is theoretically proven that self-regulation is one of the central components of critical thinking, and the interaction of these phenomena enhances the effectiveness of each of them. It is noted that the developed critical thinking and self-regulation acquire special significance in the professional activity of the police.The following methodological tools were used: test of critical thinking, methods of self-management research, methods of diagnostics of regulation focus. The sample: the first group consisted of 47 cyber police officers, the second - 51 civilian IT specialists. It has been empirically found that cyber police officers are more action-oriented in anticipation of success in difficult situations involving overcoming strong pressure; they are characterized by a better ability to maintain a positive emotional mood and not lose motivation in routine activities, and can better concentrate on the process of activity and ignore external and internal stimuli that interfere with the tasks. Cyberpolice officers show a greater focus on action, hoping for success in dealing with situations of strong external pressure, greater ability to maintain the optimal functioning of all parts of self-regulation in extreme conditions, overcome anxiety and remain focused in stressful situations. These subjects are more successful in integrating contradictions, which allows them to realistically evaluate various contradictory information and perceive contradictory experiences as a sign of real existence, to critically connect it with their own values and meanings. Representatives of this group are more characterized by the focus of prevention in self-regulation, which cyber police consider the best way to achieve the goal, which necessitates awareness, criticality and vigilance in decision-making, systematic evaluation, verification and prevention of errors, which are subjectively significant conditions . Actualization of the focus of prevention in the system of self-regulation of cyberprofessional workers causes a positive emotional coloration of the results of actions in the absence of negative results, and in case of negative consequences becomes a source of negative affective feelings, which initiates vigilance to neutralize probable losses. It is noted that the deployment of further research in the chosen direction will not only enrich the theoretical understanding of the problem, but also provide an opportunity to use the obtained empirical data in the applied psychology of policing.
Keywords: cyberpolice; critical thinking; police; self-regulation; focus of regulation.